Analysis of Understanding of First-Year Chemistry Education Students on Molecular Forces Topic - Muhammad Miqdam Musawwa; Beta Wulan Febriana; Widinda Normalia Arlianty (Universitas Islam Indonesia, 2018)
This research aims to investigate the concept understanding of first year students of study program chemistry education, faculty of mathematics and natural sciences, Universitas Islam Indonesia Yogyakarta, Indonesia. The sample used in this study was 49 students. Data collection instruments used are multiple choice questions. The results of the study show that there are still many students who have difficulty in determining the example of the force between molecules that occurs in several molecules. Students also have difficulty in determining the molecuar forces between molecules from the example case given. The level of student understanding in the material concept of moleculecular forces is classified intermediate.